Pelaksanaan Forum Wali Murid dalam Kolaborasi Sekolah Dengan Masyarakat - Suhari Muharam; Raden Bambang Sumarsono; Agus Timan (Universitas Indraprasta PGRI, 2025)
The parent forum is a space for interaction that emphasizes not only formality but also social and emotional aspects. This study focuses on examining the role of the parent forum as a platform for collaboration between the school and the community at SMP IT Asy-Syadz from November 2024 to April 2025. The objectives of the study are to examine the mechanisms for implementing the forum, map the contributions of parents, and reveal the obstacles faced in building partnerships with the school. A qualitative approach with a case study design was employed, and data were collected through in-depth interviews, direct observation, and documentation, which were then analyzed using NVivo 14 software. The study's results show that parent forums increase community involvement in supporting various educational programs. However, limitations remain apparent in the low participation of some parents, especially those residing outside Java, due to distance and work constraints. To reduce these obstacles, schools have provided accommodation facilities for parents from distant areas. In addition, parent forums have the potential to be developed through the use of digital technology, such as online meetings, and the optimization of the roles of public relations and school committees as communication mediators. This study confirms that parent forums can be a strategic instrument in establishing partnerships between schools and families, while strengthening educational success through closer collaboration.